Comparison of Balance Parameter and Muscle Strength after Anterior Cruciate Ligament Reconstruction in Professional Football Players - Gazmend Rahova, Serap Colak, Aydin Ozbek, Belgin Bamac, Pelin Ergun, Tuncay Colak, Mehmet Deniz Yener, Fatih Tezel, Yildiz Ece (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: Most ACL injuries occur during sports activities. It is aimed to compare the anthropometric measurements, muscle strength and balance abilities of the lower extremities of professional male football players who have undergone ACL surgery and completed their rehabilitation programs. Methodology: In both groups, anthropometric measurements, lower extremity muscle strengths with manual hand dynamometer and lower extremity balance measurements were made with an easytech balance device. Results: An increase in right hip flexion strength was determined in football players who had undergone ACL surgery (p<0.05). There was an increase in ipsilateral hip abduction angles in the surgical group (p<0.05). When the data of the right and left extremities of the participants in the experimental group were compared, it was determined that there was an increase in the flexion strength of the operated knee (p<0.05). When the balance data of the football players were examined, it was concluded that the right leg and double leg balance data were impaired compared to the control group (p<0.05). Conclusion: Categorizing sports injuries by type and branch of sports; it is important to determine the physical characteristics of athletes gained after treatment. We think that this approach can contribute to the design of rehabilitation programs and reduce recurrent injuries.